The conditions of self-awareness among faculty member on excellent academic services - Taufik Taufik; Ifdil Ifdil (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2019)
Supposed educators can provide excellent service to consumers, in the academic community of Universitas Negeri Padang. Universitas Negeri Padang comes in at the 61st (sixty-one) out of the 100 (one hundred) best universities in Indonesia. Being one of the best universities in Indonesia’s educators should have excellent service to consumers who in this case are students. However, in fact, many educators still do not have self-awareness (self-awareness) awareness) in providing excellent service to consumers. This is evidenced by the identification of self-awareness conditions of respondents in the high category is still low compared to the medium category. The following report will describe the condition of self-awareness of educators.